2010
DOI: 10.1002/cne.22295
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory neurons in the anterior piriform cortex of the mouse: Classification using molecular markers

Abstract: The primary olfactory cortex (or piriform cortex, PC) is attracting increasing attention as a model system for the study of cortical sensory processing, yet little is known about inhibitory neurons in the PC. Here we provide the first systematic classification of GABA-releasing interneurons in the anterior PC of mice, based on the expression of molecular markers. Our experiments used GAD67-GFP transgenic mice, in which gamma-aminobutyric acid (GABA)-containing cells are labeled with green fluorescent protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
121
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(142 citation statements)
references
References 57 publications
20
121
1
Order By: Relevance
“…S3) (27). We confirmed that interneurons comprise a small fraction (approximately 4%) of layer 2 neurons in the PC, consistent with previous reports (28). Thus, most of the neurons imaged in layer 2 are glutamatergic (SL and SP cells).…”
Section: Resultssupporting
confidence: 92%
“…S3) (27). We confirmed that interneurons comprise a small fraction (approximately 4%) of layer 2 neurons in the PC, consistent with previous reports (28). Thus, most of the neurons imaged in layer 2 are glutamatergic (SL and SP cells).…”
Section: Resultssupporting
confidence: 92%
“…Nonetheless, the increase in suppressive responses may suggest an important role for inhibitory interneurons in this plasticity. There are a variety of different classes of GABAergic interneurons in the aPCX each of which contribute differently to circuit function (Suzuki and Bekkers 2010). In naïve animals, inhibitory interneurons in piriform cortex are much more broadly odor responsive than pyramidal cells (Poo and Isaacson 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the piriform cortex, most excitatory neurons are clustered in layer II, while GABAergic interneurons are sparsely spread across all layers, as shown in Fig. 3 (Kapur et al, 1997;Ekstrand et al, 2001;Suzuki and Bekkers, 2007, 2010a, 2010b. Among excitatory neurons, semilunar cells are particularly concentrated in the outer part of layer II, where most DCX/PSA-NCAM IN can be found in the piriform cortex of mice and rats (Gómez-Climent et al, 2008;Rubio et al, 2015).…”
Section: The Number Of Dcx/psa-ncam In Declines Drastically With Agementioning
confidence: 92%